Experimental Study on Effect of Injection Pressure to Spray Characteristics, Performance and Emissions of DieselEngine DI 20 C Using Biodiesel Fuel - Alham A.K. Mahanggi; Bambang Sudarmanta; Hary Soebagyo (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2018)
Biodiesel as an alternative fuel can replace fossil fuels. However, biodiesel has a higher value of viscosity, density and surface tension to fossil fuels. Increasing the injection pressure on the injector is one solution to overcome the problem of high viscosity, density, and surface tension in biodiesel. This study aims to determine the effect of increasing injection pressure and injection timing variations on spray characteristics, performance and exhaust emissions diesel engine. Injection pressure namely 200, 210, 220, 230 kg/cm^2 by setting the rotation of adjusting screw the injector. The results of this study were obtained by increasing the pressure injection of biodiesel fuel by 230 kg/cm^2 resulting in fuel spray characteristics better than the standard 200 kg/cm^2 and resulting improvements in the penetration length, spray angle, the average diameter size of each 30%, 28%, and 9.78%. And performance improvements and exhaust emissions also occur, namely Thermal Efficiency, Specific Fuel Consumption, and Smoke Opacity with values of 16.99%, 14.15%, and 46.39% improved respectively.